2022
DOI: 10.1186/s12967-022-03684-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between triglyceride-to-high-density lipoprotein cholesterol ratio and prediabetes: a cross-sectional study in Chinese non-obese people with a normal range of low-density lipoprotein cholesterol

Abstract: Background Evidence about the relationship between triglyceride-to-high-density lipoprotein cholesterol (TG/HDL-C) ratio and prediabetes (Pre-DM) in Chinese non-obese people with a normal range of low-density lipoprotein cholesterol (LDL-c) is limited. Therefore, the present study was undertaken to explore the link of the TG/HDL-C ratio on Pre-DM among non-obese Chinese population with a normal range of LDL-c. Methods This study was a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Recent studies have shown a nonlinear correlation between TG/HDL-C ratios and the risk of CKD in American adults, pinpointing the curve’s inflection point at a TG/HDL-C ratio of 6.68 ( 39 ). Furthermore, our literature review indicates that this ratio also exhibits a nonlinear relationship with the risk of other conditions, such as in-hospital mortality from acute type B aortic dissection, arterial stiffness, the incidence of type 2 diabetes, and the onset of pre-diabetes ( 40 43 ). These studies consistently reveal that as TG/HDL-C ratios increase, the risk of disease rises but then plateaus after exceeding a certain threshold, suggesting a saturation effect.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown a nonlinear correlation between TG/HDL-C ratios and the risk of CKD in American adults, pinpointing the curve’s inflection point at a TG/HDL-C ratio of 6.68 ( 39 ). Furthermore, our literature review indicates that this ratio also exhibits a nonlinear relationship with the risk of other conditions, such as in-hospital mortality from acute type B aortic dissection, arterial stiffness, the incidence of type 2 diabetes, and the onset of pre-diabetes ( 40 43 ). These studies consistently reveal that as TG/HDL-C ratios increase, the risk of disease rises but then plateaus after exceeding a certain threshold, suggesting a saturation effect.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, HDL-C levels in prediabetic subjects were negatively connected to the likelihood of developing diabetes 17 , 18 . Moreover, lower HDL-C levels have been linked to a substantial risk factor for Pre-DM 35 , 36 . Consequently, we postulate that a decline in HDL-C levels might be linked to an augmented probability of transitioning from prediabetes to normoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high blood glucose level is an early indicator of pre-diabetes to diabetes, when the patient is diagnosed with impaired glucose tolerance (IGT) or impaired fasting glucose (IFG) ( 32 ). Next, in PreDM patients, dyslipidemia has been caused by increased LDL-C level and decreased HDL-C levels ( 33 , 34 ). Aberrantly increased LDL-C as well as decreased HDL-C may lead to dysfunction of the islet β cells, and accelerated the procedure from PreDM to type 2 DM ( 35 ).…”
Section: Discussionmentioning
confidence: 99%